2009
DOI: 10.1177/014556130908801210
|View full text |Cite
|
Sign up to set email alerts
|

An Asymptomatic Schwannoma of the Nasal Septum: Report of a Unique Case

Abstract: Schwannomas of the nasal septum are extremely rare, and therefore their diagnosis and treatment can pose certain challenges. We describe the case of an incidentally discovered schwannoma of the nasal septum that was unique in that the lesion was completely asymptomatic. In view of our finding, we believe that routine examinations of both nasal fossae should be considered during routine diagnostic laryngeal flexible endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
2
1
1
Order By: Relevance
“…Sinonasal schwannomas are reported to be equally distributed between the sexes and occur mostly in patients between the second and fifth decade of life (range, 6–82 years) . However, in our series, there was a female‐to‐male ratio of 4.5:1 with a mean age of 49.5 years.…”
Section: Discussioncontrasting
confidence: 62%
“…Sinonasal schwannomas are reported to be equally distributed between the sexes and occur mostly in patients between the second and fifth decade of life (range, 6–82 years) . However, in our series, there was a female‐to‐male ratio of 4.5:1 with a mean age of 49.5 years.…”
Section: Discussioncontrasting
confidence: 62%
“…The search yielded 52 studies and a total of 71 patients, including this reported case. 1,2,7,9 -11,13 -58…”
Section: Discussionmentioning
confidence: 99%
“…Sinonasal schwannomas are uncommon tumors that have been described as case reports or as small case series. To date, only 20 reports of nasal septum schwannoma have been reported in western literature [4] . Schwannomas of the nasal septum are extremely unusual and not many cases have been reported previously.…”
Section: Discussionmentioning
confidence: 99%